Tumors of the hand - Mavrogenis, Andreas F; Panagopoulos, Georgios N; Angelini, Andrea; Lesenský, Jan; Vottis, Christos; Megaloikonomos, Panayiotis D; Kokkalis, Zinon T; Kontogeorgakos, Vasilios; Ruggieri, Pietro; Papagelopoulos, Panayiotis J (European journal of orthopaedic surgery & traumatology, 2017)
Tumors of the hand comprise a vast array of lesions involving skin, soft tissue and bone. The majority of tumors in the hand are benign. Malignant tumors, although rare, do occur and frequently have unique characteristics in this specific anatomic location. Careful staging, histological diagnosis and treatment are essential to optimize clinical outcome. However, straightforward most of the time, hand tumor management does have pitfalls; caution is advised, as a missed or delayed diagnosis or an improperly executed biopsy may have devastating consequences. This article reviews the clinical spectrum of the most common benign and malignant bone and soft tissue tumors of the hand and discusses the clinicopathological findings, imaging features and current concepts in treatment for these tumors.
Keywords: Soft Tissue Neoplasms; nádory kůže; vaskulární nádory; Humans; Skin Neoplasms; nádory kostí; sarkom; Soft tissue; Bone Neoplasms; nádory periferního nervového systému; Giant Cell Tumor of Tendon Sheath; Ganglion Cysts; lidé; nádory měkkých tkání; staging nádorů; Sarcoma; Fibroma; obrovskobuněčný nádor šlachové pochvy; fibrom; Peripheral Nervous System Neoplasms; Tumors; Vascular Neoplasms; cystická ganglia; ruka; Neoplasm Staging; Bone; lipom; Hand; Lipoma